ARMENIANS IN THE ETHNIC LANDSCAPE OF EAST TRANSCAUCASIA IN THE SECOND HALF OF THE 18TH CENTURY - Mhitaran, Goar Zoraevna (History, Archeology and Ethnography of the Caucasus, 2022)
In the second half of the 18th century the Armenians occupied a special place in the ethnopolitical picture of East Transcaucasia. Despite a number of scientific studies carried out with the involvement of a wide range of historical sources and archival materials about the Armenians of East Transcaucasia, the subject can be still considered insufficiently studied. The choice of chronological framework is due to the fact that in the previous (16–17th centuries) and subsequent (19–20th centuries) periods, the history of the problem was comprehensively and properly covered in historiography. The present paper, by comparing Russian sources, manuscript materials of the Matenadaran archive, archival documents, based on the principles of historicism and objectivity, involving the study of the relationship of facts in specific historical conditions in chronological order, aims to recreate the most complete ethno-confessional history and the social and legal status of the Armenian population Eastern Transcaucasia in the context of political events of the second half of the 18th century. After the assassination of Nadir Shah (1747) and the collapse of his state in East Transcaucasia, a number of sovereign administrative and political units arose (Derbent, Quba, Sheki, Shemakha, Baku khanates), and the former Iranian rulers gained local power. The study shows that with the weakening of the central government in Iran in the second half of the 18th century, the ethnopolitical picture in East Transcaucasia changed. One of the consequences of these processes was the intensification of socio-economic and ethno-religious repressions against the Armenian population. The aggravation of the military-political situation in the South Caucasus at the end of the century (the invasion of Agha-Mohammed-Khan Qajar’s troops, the Persian campaign of the Russian army in 1796) led to the migration of Armenians from their places of permanent residence to the North Caucasus and the territory of the Russian Empire. As a result, the ethno-religious picture of Eastern Transcaucasia changed not in favor of Christians, in particular, Armenians.